Технологическая оценка зерна сортов и линий озимой мягкой пшеницы селекции ФГБНУ «АНЦ «Донской» - E. V. Ionova; N. S. Kravchenko; N. G. Ignatieva; N. E. Vasyushkina; I. M. Oldyreva (Зерновое хозяйство России, 2018)
Technological assessment of varieties and lines of winter soft wheat developed by the FSBSI ARC "Donskoy" The article considers the study results of physical, milling and technological traits of grain produced by the winter soft wheat varieties and lines in the Agricultural Research Center “Donskoy”. High indexes of test weight and general vitreousness of grain have been revealed. According to GOST R 52554-2006, the trait ‘test weight’ of all studied varieties met the requirements made to the grain of the grade №1, i.e. strong wheat (more than 750 g/l). According to the trait ‘general vitreousness’, the new and promising varieties met the requirements made to the grain of the grade №1 that proves the ability of these genotypes to be used as the sources of high physical traits of grain in the breeding process. There have been estimated traits that can effect on the quality of the products, namely total flour extraction, whiteness and flour ash content. The varieties ‘Shef’ (72.7%), ‘Etyud’ (72.7%), ‘Tanais’ (72.5%) and the lines ‘1491/09’ (72.5%) produced the largest amount of flour. The study has established that flour whiteness of the following varieties and lines complies with the characteristics of grain of the grade №1; they are ‘Luchezar’ (54.9 units), ‘Etyud’ (56.6 un.), ‘Kipchak’ (56.9 un.), ‘Kazachka’ (57.4 un.), ‘Bonus’ (58.8 un.), ‘1906/07’ (55.1 un.), ‘1377/07’ (55.3 un.), ‘1401/09’ (55.5 un.), ‘1127/10’ (57.7 un.), ‘1491/07’ and ‘1062/09’ (58.7 un.). According to the flour ash content, the flour of the following varieties and lines complies with the characteristics of the grain of grade №1; they are ‘Shef’ (0.34%), ‘Ermak’ (0.40%), ‘Aksiniya’ (0.40%), ‘Bonus’ (0.40%), ‘Kazachka’ (0.40%) and ‘1127/10’ (0.46%). Flour of the varieties ‘Bonus’, ‘kazachka’, ‘Luchezar’ and the line ‘1127/10’ corresponds to the properties of the grade №1 both in ash content and whiteness. Total yield of bread and general baking assessment the varieties ‘Nakhodka’ (710 ml; 4.5 points) and ‘Aksiniya’ (690 ml; 4.5 points) correspond to the properties of grain of grade №1. The varieties ‘Nakhodka’ (243.7 un.), ‘Aksiniya’ (234.7 un.), ‘Bonus’ (229.8 un.), ‘Ermak’ (226.0 un.), ‘Shef’ (204.3 un.) and the line ‘1127/10’ (204.2 un.) have demonstrated the best indexes of the technological potential, that proves their promising use in making bread of good quality. The extracted varieties and lines can be used as the sources of high qualitative grain and baking properties in the breeding process.